Constipation: an emerging risk factor for Parkinson's disease?. (22nd July 2016) - Stirpe, P.; Hoffman, M.; Badiali, D.; Colosimo, C.
Abstract : Constipation is the most prominent and disabling manifestation of lower gastrointestinal (GI) dysfunction in Parkinson's disease (PD). The prevalence of constipation in PD patients ranges from 24.6% to 63%; this variability is due to the different criteria used to define constipation and to the type of population enrolled in the studies. In addition, constipation may play an active role in the pathophysiological changes that underlie motor fluctuations in advanced PD through its negative effects on absorption of levodopa. Several clinical studies now consistently suggest that constipation may precede the first occurrence of classical motor features in PD. Studies in vivo, using biopsies of the GI tract and more recently functional imaging investigations, showed the presence of α‐synuclein (α‐SYN) aggregates and neurotransmitter alterations in enteric tissues. All these findings support the Braak proposed model for the pathophysiology of α‐SYN aggregates in PD, with early pathological involvement of the enteric nervous system and dorsal motor nucleus of the vagus. Therefore, constipation could have the potential sensitivity to be used as a clinical biomarker of the prodromal phase of the disease. The use of colonic biopsies to look at α‐SYN pathology, once confirmed by larger prospective studies, might eventually represent a feasible, albeit partially invasive, new diagnostic biomarker for PD.